2008
DOI: 10.1074/jbc.m709186200
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of the Human DNA Glycosylase NEIL1 with Proliferating Cell Nuclear Antigen

Abstract: NEIL1 and NEIL2 compose a family of DNA glycosylases that is distinct from that of the other two DNA glycosylases, OGG1 and NTH1, all of which are involved in repair of oxidized bases in mammalian genomes. That the NEIL proteins, unlike OGG1 and NTH1, are able to excise base lesions from single-stranded DNA regions suggests their preferential involvement in repair during replication and/or transcription. Previous studies showing S phase-specific activation of NEIL1, but not NEIL2, suggested NEIL1 involvement i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
91
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 128 publications
(99 citation statements)
references
References 60 publications
7
91
1
Order By: Relevance
“…Consistent with these observations, physical and functional interactions between human UNG2 and PCNA in vitro were confirmed with the purified proteins (16). Besides UNG2, several DNA glycosylases reportedly interact with PCNA (17)(18)(19). It is widely known that many other replicative and repair enzymes interact with PCNA, via a consensus sequence called the PCNA-interacting protein (PIP) box (15).…”
supporting
confidence: 59%
“…Consistent with these observations, physical and functional interactions between human UNG2 and PCNA in vitro were confirmed with the purified proteins (16). Besides UNG2, several DNA glycosylases reportedly interact with PCNA (17)(18)(19). It is widely known that many other replicative and repair enzymes interact with PCNA, via a consensus sequence called the PCNA-interacting protein (PIP) box (15).…”
supporting
confidence: 59%
“…2D). Dou et al (45) recently showed that proliferating cell nuclear antigen also interacts with and stimulates NEIL1 incision activity. However, in that study proliferating cell nuclear antigen stimulated NEIL1 incision activity up to 3-fold at a much higher molar excess of proliferating cell nuclear antigen (ϳ1:83.3).…”
Section: Resultsmentioning
confidence: 99%
“…S2) and others have described overexpression of the edited form (R242) in mammalian cells (30,33). In addition, several studies using edited NEIL1 have shown that removal of 5-OHU or FapyG by NEIL1 is enhanced by the presence of protein-binding partners (e.g., PCNA, FEN1, and CSB) (33)(34)(35). The stimulatory affects afforded by protein partners may depend on the form of NEIL1 used as well as the nature of the lesion and its nucleic acid context.…”
Section: Discussionmentioning
confidence: 99%